Pengaruh Penerapan Keselamatan dan Kesehatan Kerja (K3) Terhadap Efektivitas Pencegahan Kecelakan Kerja - Novika Candra Fertilia (Rekayasa Sipil, 2020)
Project Constructions are unique, safety or security and protection factors at work become one of the most important factors of work productivity (Hanafi, 2017). Occupational safety and health have a contribution value of up to 20.2% on performance (Kartikasari, 2017). In the implementation of building projects by PT. XY found a lack of awareness of workers in the use of equipment and safety equipment, this is evident from the lack of use of protective fences and also signs/warning signs that are not fully installed. This research will discuss what are the dominant risks that influence the implementation of OHS management at PT. XY. Based on these dominant risks, this reaserch will create a safety execution development based on the Construction Extension to PMBOK Guide - 2016 Edition.